S86 Change in patient demographics and Home Mechanical Ventilation (HMV) set up for patients with chronic respiratory failure between 2006 and 2012. (14th November 2013) - Drake, S; Ramsay, M; Steier, J; Hart, N
Abstract : Introduction: HMV is standard therapy for long term management of chronic respiratory failure in patients with neuromuscular disease (NMD), chest wall disease (CWD), chronic obstructive pulmonary disease (COPD) and obesity related respiratory failure (ORRF). This study investigated changing trends in patient demographics and HMV ventilator set up over a 7-year period. Methods: Data from a bespoke discharge summary system (Carevue, Philips Corporation, US) of patients established on HMV from 2006 to 2012 were analysed. Patient demographic and anthropometric data, including spirometry and arterial blood gas values were analysed. Difference in length of stay (LOS) for non-invasive ventilation (NIV) set up and trends in the ventilator pressures was performed. A p-value <0.05 was considered significant. Results: 952 patients (518 male) were reviewed with a mean age of 57 ± 16 years. HMV set ups rose by 32.1% over the 7 years. The largest increase was observed in the ORRF group from 44% to 53% of the cohort. In comparison with 2006, NMD/CWD patients were started on HMV with lower arterial partial pressure of carbon dioxide (Pa CO2 ) in 2012, whilst COPD patients were initiated on HMV at a higher Pa CO2 (Table 1 ). LOS for elective NIV set up fell between 2006 and 2012 (4 (2–7) vs 2 (1–3) days; <0.0001). An increase in inspiratory positive airway pressure (IPAP) was demonstrated across all groups with a decrease in expiratory positive airway pressure (EPAP) demonstrated in NMD/CWD and COPD groups (Table 1 ). Conclusions: This study demonstrated an increasing demand for HMV in the UK. This was most marked in the ORRF group in line with rising levels of obesity. In 2012, NMD/CWD patients were being initiated on HMV earlier in the course of chronic respiratory failure, whereas COPD patients were being initiated when chronic respiratory failure was well established. A significant increase was observed in the inspiratory pressures delivered across all groups with a reduction in the expiratory pressures in the NMD/CWD patients as well as the patients with COPD. Efficiency of HMV set up has improved, as reflected by the reduced LOS and this is the result of a more structured clinical pathway.